2019
DOI: 10.5812/ijcm.90225
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Behavioral Control in Mammography: A Qualitative Study of Iranian Women’s Experiences

Abstract: Background: Mammography is one of the best methods to screen breast cancer. Because mammography screening is not entirely under the control of the person, the study of perceived behavioral control (PBC) is valuable in this regard. Objectives:The aim of this study was to investigate PBC in mammography in women in Khorramabad, Lorestan province, Iran (550 kilometers north of Persian Gulf). Methods: In this qualitative study conducted using semi-structured and in-depth interviews, 22 women, a gynecologist, and a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…That's why they are diagnosed at the last stage when there is the only option of surgery [35][36][37][38]. Similarly in Iran embarrassment, fear of breast cancer diagnosis, and belief in fate were the major reported barriers by females to breast cancer screening [39]. In addition, the study conducted in Canada reported the uncomfortable feeling of women while discussing breast cancer screening as a barrier to the screening of breast cancer.…”
Section: Plos Onementioning
confidence: 99%
“…That's why they are diagnosed at the last stage when there is the only option of surgery [35][36][37][38]. Similarly in Iran embarrassment, fear of breast cancer diagnosis, and belief in fate were the major reported barriers by females to breast cancer screening [39]. In addition, the study conducted in Canada reported the uncomfortable feeling of women while discussing breast cancer screening as a barrier to the screening of breast cancer.…”
Section: Plos Onementioning
confidence: 99%
“…These were based on a woman’s role in the household (Theme 1.1.1); women were expected to prioritise looking after their family’s needs and managing domestic responsibilities due to their position as wives and mothers ( Macdonald et al, 2015 , Urrutia et al, 2017 , Yang et al, 2019 , Trigoni et al, 2008 , Nyblade et al, 2017 , Thomas et al, 2011 , Safizadeh et al, 2018 , Shirzadi et al, 2020 , Rasul et al, 2015 , Baron-Epel et al, 2004 , Azaiza and Cohen, 2008 , Ngugi et al, 2012 , Wong et al, 2008 , Markovic et al, 2005 , Khan and Woolhead, 2015 , Daley et al, 2012 , Filippi et al, 2013 , Tessaro et al, 1994 , Nekhlyudov et al, 2003 , Nolan et al, 2014 , Nonzee et al, 2015 ). Women in the included studies also expressed that there were sociocultural expectations on female behaviour (Theme 1.1.2); they were expected to care for others’ health above their own ( Trigoni et al, 2008 , Wong et al, 2008 , Filippi et al, 2013 , Tessaro et al, 1994 , Thomas et al, 2011 , Safizadeh et al, 2018 , Shirzadi et al, 2020 , Rasul et al, 2015 , Nolan et al, 2014 , Nonzee et al, 2015 , McMichael et al, 2000 , Manderson and Hoban, 2006 , Dey et al, 2016 , Savabi-Esfahani et al, 2018 , Khazaee-pool et al, 2014 , Khazir et al, 2019 ), and were expected to have a sense of modesty that was incompatible with the bodily exposure required during breast or cervical screening ( Macdonald et al, 2015 , Azaiza and Cohen, 2008 , Isa Modibbo et al, 2016 , Püschel et al, 2010 , Ndejjo et al, 2017 ). However, women in several studies also mentioned that there was a motivation to engage in cancer screening in order to stay healthy for the sake of their family.…”
Section: Resultsmentioning
confidence: 99%
“…It is this normative perception of privilege or exclusiveness that causes men and women to feel uncomfortable with the perceived inappropriateness about interactions involving a woman’s sexual organs that are not specifically with her husband. In addition to the fear of being seen as promiscuous due to the nature of cervical cancer, women reported that these two cancers – and female health issues in general – were generally taboo topics that should not be discussed except in private ( Thomas et al, 2011 , Azaiza and Cohen, 2008 , Khan and Woolhead, 2015 , Khazir et al, 2019 , Bayrami et al, 2015 , Malhotra et al, 2016 , Lunsford et al, 2017 , Shaw et al, 2018 , Onyenwenyi and Mchunu, 2018 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Khazir quotes from the WHO, 2015, in poor communities, most women are diagnosed with late-stage disease and their 5-year survival rate is 10 to 40%. In more developed communities, where the disease is diagnosed and treated in the early stages, the 5-year survival rate reaches 80% [5] . Annually, more than 1.1 million new cases of breast cancer are diagnosed globally, and over 41,000 deaths occur as a result of the disease [6] .…”
Section: Introductionmentioning
confidence: 99%